1992
DOI: 10.1016/0378-1097(92)90526-t
|View full text |Cite
|
Sign up to set email alerts
|

Lipid accumulation in Trichoderma species

Abstract: Two filamentous fungi, Trichoderma harzianum and Trichoderma viride, were compared for their ability to synthesize lipids on different carbon and nitrogen sources. Three culture media were selected for each strain after preliminary screening. All the test media were nitrogen‐deficient (C/N = 60) so as to stimulate lipid accumulation. For both microorganisms the glucose‐ammonium sulphate medium was the most conducive to lipid production: a lipid accumulation of 17% (w/w) of biomass dry weight was obtained for T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…These values are in agreement with previous studies concerning lipid synthesis by T. viride [8] and T. reesei [24]. Nevertheless, lipid accumulation in Trichoderma terrestrial strains were shown very dependent of different parameters as the culture media composition [10], the pH and the temperature Data are the mean of three replicates AE S.D. a As explained in Section 2, expressed per litre of culture.…”
Section: Biomass Total Lipid Content and Lipid Classessupporting
confidence: 89%
See 4 more Smart Citations
“…These values are in agreement with previous studies concerning lipid synthesis by T. viride [8] and T. reesei [24]. Nevertheless, lipid accumulation in Trichoderma terrestrial strains were shown very dependent of different parameters as the culture media composition [10], the pH and the temperature Data are the mean of three replicates AE S.D. a As explained in Section 2, expressed per litre of culture.…”
Section: Biomass Total Lipid Content and Lipid Classessupporting
confidence: 89%
“…In both culture ways, linoleic acid was the highest FA in TL as well as in PL. Similar amounts of linoleic acid has been reported in other Trichoderma species cultivated in liquid medium as T. reseii (47%) [11] and T. harzianum (48%) [10]. In both fermentations stearic acid was present in smaller levels in PL, showing that it likely does not play any structural role in the cell membrane.…”
Section: General Comparison Of Fa Composition Of T Longibrachiatum Isupporting
confidence: 64%
See 3 more Smart Citations